The ambivalence of an Anglophile subject in Kam Raslan’s confessions of an old boy: The Dato’ Hamid Adventures - Abd Razak, Mohd Shukri; Mohd Nasir, Nora; Abdul Kadir, Maimunah; Ahamad Shah, Mohamed Ismail (International Islamic University Malaysia, 2019)
This paper focuses on ambivalence, a prominent concept in postcolonial studies and a recurrent theme in an anglophile subject in Kam Raslan’s novel, Confessions of an Old Boy: The Dato’ Hamid Adventures(2007). As a result of ambivalence, the anglophile subject feels alien in his perception of himself and also towards others. The subject is also ambivalent towards his own culture. Using this framework, this article focuses on Kam Raslan’s protagonist, Dato’ Hamid, as an ambivalent anglophile subject. The findings reveal that reverence for the English culture, coupled with a British colonial education is what gives rise to such characters. It is the British education that has indoctrinated English values into the native’s life. The admiration of the anglophile towards the “English” culture can be seen in many aspects, such as language, dress code, behaviour, relationships, lifestyle, etc. All these elements become traits and characteristics of the anglophile. The study reveals the adoption, adaptation and assimilation of English traits and characteristics by the anglophile subject which has caused a sense of ambivalence in his perception of himself and towards the “other.”